Young Researchers' Forum proceedings of the international conference held at the University of Dundee, Scotland, UK on 7 July 2005 - Dhir, Ravindra K.; Halliday, Judith E.; Csetenyi, Erika (Thomas Telford, 2005)
Topics addressed by this volume include: opportunities for concrete research; bond strength in self-consolidating concrete; determining material parameters concerning the design of concrete pavements; self compacting light concrete with liapor aggregates; and re-use of GRP industrial waste in cementitious products.